SELEKSI SENYAWA PENGHIDROLISIS UNTUK MENGHASILKAN GULA REDUKSI DARI LIMBAH KULIT ARI KEDELAI SEBAGAI BAHAN FERMENTASI BIOETANOL - Zulkifliani, Zulkifliani; Handayani, Siska; Adisyahputra, Adisyahputra; Sakarani, Devitra (LPPM Universitas Negeri Jakarta, 2017)
This study aims to determine the most effective compound used to hydrolyze soy husk waste to produce reducing sugar as raw material for bioethanol fermentation. The study was conducted at the Laboratory of Bioprocess PPPTMGB